Intention to use AI in accounting education: an analysis from the TAM and TPB perspectives - Gaviria Rodríguez, Diana Yanet; Valencia-Arias, Alejandro; Arango Arango, Juan Guillermo; Raunelli Sander, Juan Manuel; Verde Flores, Lilian; Valencia, Jackeline (Frontiers in Education, 2025)
IntroductionThis study examines the integration of Artificial Intelligence (AI)-based tools into university-level accounting education in Medellín, Colombia. The objective was to identify the factors that influence students' intention to adopt these technologies, using theoretical frameworks such as the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM).MethodsAn experimental methodology was applied, which included the development of an educational video incorporating AI and an accounting simulator. A total of 105 students participated in the study and completed a Likert-type questionnaire designed to evaluate constructs including attitude, perceived usefulness, ease of use, subjective norm, and behavioral control.ResultsThe analysis revealed that perceived ease of use significantly influenced both perceived usefulness and behavioral control. Additionally, subjective norm had an impact on attitude and intention to use. However, perceived usefulness did not translate into favorable attitudes toward AI adoption, indicating a gap between the functionalities students recognized and their expectations of the technology.DiscussionThe findings highlight the importance of contextualizing AI functionalities within educational settings. They suggest the need for pedagogical strategies that align technological tools with students' expectations and foster a more receptive environment toward digital innovation in accounting education.